“A Study of Teachers’ Preference of Teaching Methods.” - Gupta, Jyoti (IJRDO- Journal of Educational Research, 2017)
The objective of the study was to assess the preference of teaching methods used by seniorsecondary teachers in Bareilly city. The total sample consists of 114 teachers in which 73from general, 41 from vocational courses. Among these 67 were male teachers and 47 werefemale teachers. This sample was further categorized in on the basis of teaching streamarts(36), commererce (19), science(35) and technical(24), selected through stratifiedrandom sampling technique to obtain data for investigation. A self constructedquestionnaire was used to collect data. After analyzing data, studied revealed that mostpreferred and opted methods by teachers at higher secondary level were lecture, chalk andtalk, assignment, textbook, demonstration and problem solving methods.